THE OVERVIEW OF MAXILLARY AND MANDIBULARY MESIODISTAL TEETH SIZE OF MEN AND WOMEN ON BANJARNESE PEOPLE - DH, Irnamanda; Wibowo, Diana; Malinda. M, Okky (FKG Unlam, 2017)
ABSTRACTBackground: Malocclusion is a deviation from normal occlusion therefore, it needs an orthodontic treatment plan. Mesiodistal tooth widths can help provide information before the treatment in dentistry. Variation of dental mesiodistal width is caused by factors of race, genetics, ethnicity, gender, environmental and disease. Purpose: This research aimed at geting an overview of dental mesiodistal size of the maxilla and mandibula in men and women Banjarnese population. Methods: This research was a descriptive using a cross-sectional design. The sampling method used purposive sampling technique. The samples amounted to 40 women and 40 men in banjarnese population with age range between 17 - 22 years. Measurement dental mesiodistal size was done by using digital caliper. Result: The result showed the average size of dental mesiodistal maxilla and mandibular in men was larger than size in women of Banjarnese population. Conclusion: It can be concluded that the average size dental mesiodistal maxilla and mandible in men was larger than size in women of Banjarnese population.Keywords: Dental mesiodistal size, banjarnese population